Germination and Seedling Growth of Water Primroses: A Cross Experiment between Two Invaded Ranges with Contrasting Climates - Gillard, Morgane; Grewell, Brenda J.; Futrell, Caryn J.; Deleu, Carole; Thiébaut, Gabrielle (Frontiers in Plant Science, 2017)
Aquatic ecosystems are vulnerable to biological invasions, and will also be strongly impacted by climate change, including temperature increase. Understanding the colonization dynamics of aquatic invasive plant species is of high importance for preservation of native biodiversity. Many aquatic invasive plants rely on clonal reproduction to spread, but mixed reproductive modes are common. Under future climate changes, these species may favor a sexual reproductive mode. The aim of this study was to test the germination capacity and the seedling growth of two water primrose species, Ludwigia hexapetala and Ludwigia peploides, both invasive in Europe and in the USA. We performed a reciprocal transplant of seeds of L. hexapetala and L. peploides from two invasive ranges into experimental gardens characterized by Oceanic and Mediterranean-type climates. Our results showed that higher temperatures increased or maintained germination percentages and velocity, decreased survivorship of germinants, but increased their production of biomass. The origin of the seeds had low impact on L. hexapetala responses to temperature, but greatly influenced those of L. peploides. The invasiveness of water primroses in ranges with Oceanic climates might increase with temperature. The recruitment from seed banks by these species should be considered by managers to improve the conservation of native aquatic and wetland plant species.